Effect of Buserelin on corpus luteum activity and the fertility of dairy cows - SARATSIS (Φ. ΣΑΡΑΤΣΗΣ) Ph.; SCHMIDT-ADAMOPOULOU (Β. SCHMIDT-ΑΔΑΜΟΠΟΥΛΟΥ) B.; YPSILANTIS (Π. ΥΨΗΛΑΝΤΗΣ) P.; BROZOS (Χ. ΜΠΡΟΖΟΣ) Ch.; DEMERTZIS (Α. ΔΕΜΕΡΤΖΗΣ) A. (Journal of the Hellenic Veterinary Medical Society, 2018)
112 selected Friesian dairy cows that had calved at least once, were used. The animals were divided into two groups, A (n = 55) and Β (n=57). On the 12th day post insemination (p.i.) 12 μg buserelin (3ml Receptal - Hoechst) and 3 ml normal saline (placebo) were injected intramuscularly to the animals of groups A and Β (controls), respectively. Milk progesterone concentration was measured in even animal from the day of insemination until the 24th day p.i.. A significant increase (P<0.05) in pregnancy rate (19.7%) was observed in the animals of group A. Also, the concentration of progesterone in the pregnant animals (14th - 24th day p.i.) as well as in the non pregnant (14th - 16th day p.i.) ones in group A was significantly increased (P<0.05) compared to that of the controls’. The duration of the estrous cycle of the non pregnant animals did not differ significantly (P>0.05) between the two groups. It is concluded that buserelin administration on the 12th day p.i. improved the fertility of dairy cows significantly by means of an antiluteolytic effect, through an increase in progesterone concentration, during the crucial period of maternal recognition of pregnancy.